ผลกระทบจากวิกฤตเศรษฐกิจปี 2540 ต่ออัตราส่วนทางการเงิน - นวลนภา วิบูลรังสรรค์ (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
Financial ratios are generally the tool for financial statement analysis. However, there are limitations of financial ratios including factors to be considered in the analysis such as size, industry’s characteristic, and economic. This thesis examines the impact of economic crisis in 1997 on financial ratios. This study uses risk ratios and profitability ratios to test the difference of financial ratios between before and after the economic crisis in 1997 and to examine the impact of size and industry characteristic on financial ratios. This study aims to statistically confirm the differences of financial ratios between before and after the economic crisis in 1997 and provide guidance to the users on the impact of economic crisis on financial ratios in order to improve the comparison of financial ratios. The results indicate that economic crisis has the impact on risk ratios. More specifically, debt ratio and current ratio before and after the economic crisis in 1997 are significantly different and these ratios present an increase in risk. However, there is no significant difference in cash flows from operation to total debt ratio. For profitability ratios, there are significantly differences in return on assets and retained earnings to total assets, and these ratios indicate the decrease in profitability. Nonetheless, the difference between before and after 1997 crisis have not found for the operating income to total assets and the cash flows from operation to net income ratios. Although the economic crisis results in an increase in risk, the industry characteristic does not found to affect the increase in risk. On the contrary, size is found to have an impact on the degree of an increasing risk. The cash flows from operation to total debt is the only ratio that does not have an impact from both industry characteristic and size. For profitability ratios, the return on assets is the only ratio that the change in ratio of the Hotel and Traval industry is significantly different from the change in such ratios of the Property Development industry. In sum, the results show that the economic crisis in 1997 has the impact on financial ratios that calculated from items adjusted for economic crisis especially the impact from foreign exchange. Ratios that calculated from items that are not adjusted for economic crisis such as cash flows from operation would help in making better ratios comparison.